Thriving in scrubs: a qualitative study of resident resilience - Abigail Ford Winkel; Anne West Honart; Annie Robinson; Aubrie-Ann Jones; Allison Squires (BMC, 2018)
Abstract Background Physician well-being impacts both doctors and patients. In light of high rates of physician burnout, enhancing resilience is a priority. To inform effective interventions, educators need to understand how resilience develops during residency. Methods A qualitative study using grounded theory examined the lived experience of resilience in residents. A cohort of obstetrics and gynecology residents were selected as a purposive, intensity sample.. Eighteen residents in all years of training participated in semi-structured interviews. A three-phase process of open coding, analytic coding and thematic analysis generated a conceptual model for resilience among residents. Results Resilience among residents emerged as rooted in the resident's calling to the work of medicine. Drive to overcome obstacles arose from personal identity and aspiration to professional ideals. Adversity caused residents to examine and cultivate coping mechanisms. Personal connections to peers and mentors as well as to patients and the work helped buffer the stress and conflicts that present. Resilience in this context is a developmental phenomenon that grows through engagement with uncertainty and adversity. Conclusion Resilience in residents is rooted in personal and professional identity, and requires engagement with adversity to develop. Connections within the medical community, finding personal fulfillment in the work, and developing self-care practices enhance resilience.